Factors influencing neonatal thyroid-stimulating hormone concentrations as a measure of population iodine status - Clapin, H.; Lewis, B.; Greed, L.; Dawkins, Hugh; O'Leary, Peter (De Gruyter, 2014)
Background: The World Health Organization (WHO) has recommended measurement of neonatal thyroid-stimulating hormone (TSH) as a marker of population iodine status. A population is considered iodine sufficient when <3% of neonatal blood samples collected 3-4 days after birth have TSH concentrations >5 mIU/L. However, changes in technology and clinical practices have opened the WHO criteria to various interpretations. Aim: This study aimed to investigate the effects of time of sampling, weight, and sex on neonatal TSH concentrations by analyzing neonatal TSH data, based on the WHO criteria for population iodine sufficiency. Methods: We analyzed the Western Australian (WA) Newborn Screening Program records for 198,826 babies born in WA between 2005 and 2011, to determine the relationship between neonatal TSH concentrations and time of sampling, weight, and sex. Results: The proportion of TSH results above the WHO cut-off was higher for samples collected 48-72 h after birth rather than later, for males, for birth weights below 2500 g, and when a cut-off of 5.0 mIU/L was used. Conclusion: Following changes in newborn screening protocols and earlier collection of blood samples, the WHO criteria appear inappropriate. We recommend that WHO revise current guidelines regarding use of neonatal TSH for monitoring population iodine status.